The experience of wearing compression garments after burn injury: "On the inside it is still me". Issue 6 (September 2019) - Coghlan, Nicole; Copley, Jodie; Aplin, Tammy; Strong, Jenny
Highlights: Over time, patients adapt to uncomfortable sensations associated with garment wear. Patients want early and ongoing education and support from peers. Diverse events, circumstances and activities lead to garment removal. Individual experiences highlight the need for patient centred service provision. Abstract: Background: Compression garments are widely used for the management of hypertrophic scars, however, the patient experience of wearing compression garments remains minimally explored. Objective: To gain an understanding of the patient experience of wearing compression garments post burn injury, including why patients remove their garments. Method: Interpretive description was the methodological approach used in this study. Semi-structured interviews and a focus group were used to gain in-depth insights into the lived experience of wearing compression garments. Thematic analysis revealed key themes across the data and member checking confirmed data interpretation. Results: Three main themes related to wearing compression garments were identified: what it feels like to wear compression garments, what it is like to be a patient within a burns service and the impact of garments on patients' lives and recovery. Conclusions: The results highlighted a variety of influences that affected the individual experience of garment wear, highlighting the need for a patient centred approach by burn service providers.